A review of knowledge, attitudes and practices regarding mosquitoes and mosquito-borne infectious diseases in nonendemic regions - Duval, Pénélope; Aschan-Leygonie, Christina; Valiente Moro, Claire (Frontiers in Public Health, 2023)
Mosquito-borne infectious diseases (MBIDs) present significant public health risks within tropical and subtropical regions. However, the rapid spread of MBIDs from these areas to temperate regions increase the risk of their emergence in nonendemic regions i.e., regions where diseases are still sporadic and not sustained in the population. Raising awareness about preventive measures and protective behaviors is of primary importance to face the risks of vector-borne diseases. In this context, the number of studies on knowledge, attitude, and practice (KAP) about mosquitoes and MBIDs has grown rapidly in response to the need to identify knowledge and practices in nonendemic countries to fight mosquito proliferation. Building upon the recent developments in this field, we conducted the first-ever literature review to examine KAP studies conducted in nonendemic regions. Our aim was to identify the community's knowledge and attitudes that shape practices concerning the prevention of MBIDs. We used specific keywords regarding the scope of this review and then selected studies that were performed in nonendemic regions for MBIDs, including regions located in European countries, the USA or Asia. We identified 32 KAP studies, the oldest from 2003. The findings in the reviewed studies show that survey participants generally possessed a rather good understanding of mosquito breeding sites. However, there were notable variations in knowledge and perception of MBIDs, primarily linked to the geographic location of the survey and the prevalence of infectious outbreaks related to mosquito transmission. These findings highlight the significant influence of knowledge and awareness in fostering effective mosquito control practices. Moreover, socioeconomic status, particularly educational attainment, and respondents' gender emerged as key determinants in explaining the variability of appropriate practices. The survey results thus show the crucial role of knowledge, emphasizing the need for widespread awareness and information campaigns, encompassing both appropriate practices and efficient mosquito control methods. Understanding the interaction between these factors could provide good guidelines for implementing awareness plans and ultimately motivate the population to actively fight against mosquito proliferation and MBIDs development.